Construction of a nomogram with IrAE and clinic character to predict the survival of advanced G/GEJ adenocarcinoma patients undergoing anti-PD-1 treatment - Wang, Han; Chen, Jinhua; Gao, Wei; Wu, Yilan; Wang, Xinli; Lin, Fangyu; Chen, Hao; Wang, Yao; Jiang, Tao; Pan, Zhangchi; Gao, Xinyan; Liu, Qing; et al. (Frontiers in Immunology, 2024)
Objective: This study aimed to develop and validate a survival prediction model and nomogram for patients with advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma treated with anti-programmed cell death 1 receptor (PD-1). The model includes immune-related adverse events (irAEs) and common clinical characteristics as predictive factors. Methods: A dataset of 255 adult patients with advanced G/GEJ adenocarcinoma was assembled. Significant irAEs affecting overall survival (OS) were integrated as a variable named "Protective irAE". Landmark analysis mitigated timing bias related to irAEs. 12 other variables were selected as candidate variables to construct the model. LASSO regression performed variable selection, and the variance inflation factor addressed multicollinearity. the forward likelihood ratio Cox regression was used to developed the model, excluding variables violating the proportional hazards assumption. The model was internally validated through bootstrap resampling and externally validated with a cohort from another hospital. Results: irAEs from the skin and endocrine systems were consolidated as protective irAE. The finalized model included seven variables: tumor stage, first-line anti-PD-1 treatment, peritoneal metastasis, Eastern cooperative oncology group performance status (ECOG PS) score, human epidermal growth factor receptor 2 (HER2) expression status, and controlling nutritional status (CONUT) score, and protective irAE. The model's concordance index was 0.66. Calibration and clinical decision curve analyses verified its accuracy and net benefit for 1- and 2-year survival rates. Conclusion: This study developed a prognostic prediction model integrating irAEs and common clinical characteristics, demonstrating good clinical practicality and accurate OS prediction for advanced G/GEJ adenocarcinoma patients. Eastern cooperative oncology group performance status (ECOG PS) score, human epidermal growth factor receptor 2 (HER2) expression status, and controlling nutritional status (CONUT) score.